Criação e repressão: Caio Fernando Abreu e a censura no Brasil da segurança nacional - Bonaldo, Deivis Jhones Garlet (2014)
This study is inserted in jurisdiction of literary studies of comparative literature and social criticism. Accordingly, in addition to find an explanation of aesthetic specificity, we believe in the significant importance of extra-aesthetic in construction of literary text as an object-sign carrying an axiological position and potentially ideological and therefore, the relation between literature and history. It is with this way of understanding that we approach our object of study, the work "O ovo apunhalado" by Caio Fernando Abreu, in context of Brazilian military dictatorship, greatly aiming to elucidate the reasons why certain stories were censored. In order to achieve our purpose, we appealed to theoretical concepts aligned with marxism and the ideas of Bakhtin Circle, as structural and superstructural relations, dialogism, ideological environment, reflection and refraction to a comprehension of context of production and the uniqueness of artistic construction. The understanding of censorship as an integral object-sign of ideological environment that surrounded the writer, we compared vetoed narratives to legislation about censorship, being possible for us to objectify possible reasons that led to prohibition without falling into subjectivism. Thereby, we perceived Caio Fernando Abreu work as a symbolic counterpoint to authoritarianism of military government, especially to express, articulating form and content, unwanted themes by government according to National Security rhetoric. The work is divided in three chapters: the first is devoted to a critical review of critical fortune about the author analyzed and to exposition of dialogism concept; the second one outlines theoretical and methodological bases and the third excels on the construction of plausible explanation for censorship in the book "O ovo apunhalado , making a possible reading of forbidden narratives and comparison with laws regarding censorship.